Uso de la gamificación como estrategia didáctica en el área de Lengua y Literatura para generar la motivación y atención en los niños de cuarto grado EGB de la Unidad Educativa Fiscomisional San Francisco de Asís de la ciudad de Loja, año lectivo 2022-2023. - Fierro Loaiza, Josselyn Alexandra (2023)
Gamification is used as a didactic strategy to improve the teaching-learning process, through active participation, motivation and the promotion of critical thinking. For its application it is essential to take into account the elements that compose and select those that adjust to the educational needs and the objective set to be met. The present investigation searched to know the use of gamification as a didactic strategy in the area of Language and Literature to generate motivation and attention in children of fourth grade of Basic General Education of the San Francisco de Asís Fiscomisional Educational Unit of the city of Loja in the school year 2022-2023. The methodology used is in accordance with the Regulation of the Academic Regime, art. 216 of the National University of Loja of the year 2021, the method used is deductive with a quantitative approach and an exploratory - descriptive scope. Twelve strategies were identified that educators use in their gamified activities to generate motivation and attention, in addition, were defined the main didactic strategies of gamification applied in the area of Language and Literature, the strategies that generate motivation and attention in children are: participation in competitions, completing missions, obtaining rewards, the story, time, sounds, scenery and characters of the game. Keywords: Gamification, Education, Didactic Strategies, Motivation, Attention